Research Notes: Using Relative Deprivation Theory to Explain Satisfaction With Income and Pay Level: A Multistudy Examination - Sweeney, Paul; McFarlin, Dean B.; Inderrieden, Edward J. (Academy of Management Journal, 1990)
This article reports four studies in which we applied relative deprivation theory to the prediction of satisfaction with income and pay level. The proposed model specified both social comparisons and a variety of self-comparisons as important for understanding satisfaction. Using four large samples of respondents and various measurements of the theoretical constructs of interest, we found considerable support for the model. Implications for future research are discussed.